Impact of the COVID-19 pandemic on hospital admission rates for arterial hypertension and coronary heart disease: a German database study - Sasko, Benjamin; Matiakis, Marios; Seibert, Felix S.; Pagonas, Nikolaos; Hippe, Hans-Jörg; Babel, Nina; Ukena, Christian; Westhoff, Timm H. (Frontiers in Cardiovascular Medicine, 2024)
Background During the SARS-CoV-2 pandemic it was speculated that the virus might be associated with a persistent increase of cardiovascular risk. The present study compares pre- and post-pandemic hospital admission rates for hypertension and coronary artery disease. Methods Systematic multicentric retrospective cohort analysis of 57.795 hospital admissions in an urban region in Germany during two different periods (pre-pandemic 01–06/2019 vs. post-pandemic era 01–06/2023). Information on hospital admissions for arterial hypertension, chronic coronary syndrome, unstable angina pectoris and acute myocardial infarction were extracted from the hospitals data systems. Additionally, six comorbidities and performed coronary interventions were monitored. Results Compared to the pre-pandemic era, there was no increase in hospitalizations for arterial hypertension (516 vs. 483, −6.8%, p = 0.07) or myocardial infarction (487 vs. 349, −23.8%, p < 0.001), but the total number of patient admissions with chest pain as the presenting symptom increased (chronic coronary syndrome: 759 vs. 943, +24.2%, p < 0.001; unstable angina pectoris: 270 vs. 451, +67.0%, p < 0.001). At the same time, the number of performed coronary angiographies increased, but less patients underwent percutaneous interventions. Patients admitted with chest pain in the post-pandemic era were in general healthier with less comorbidities. Conclusion The present multicenter cohort study found no evidence for an increase in hospitalizations for arterial hypertension or coronary artery disease after the end of the pandemic. However, further studies with larger sample sizes are needed to confirm our results.